Cultural & Knowledge Spaces: the Immersive Museums as a Challenge for KO and the Digital Humanities - Fadoua Boulakal; Widad Mustafa El Hadi (Informatio, 2025)
In this paper we discuss the place of museums in Information Science landscape and their historical role in preserving and accessing cultural heritage. Definitions of Culture, cultural heritage and more related concepts are reviewed and examined. The scope of this paper is limited to digital museums and more specifically, immersive museums. The main questions we raise are as follows: How do immersive museums, thanks to digital technologies, redefine the protection and dissemination of knowledge while addressing the socio-cultural needs for inclusion of diverse and neuro-atypical audiences? Do the new immersive mediations risk reducing the transmission of knowledge to simple communication or a spectacle, sometimes far removed from the issues of heritage preservation? Or is it an 'experience' that, while close to reality, diverges from it? The notion of 'reality' in the immersive museum may seem paradoxical: is the technological illusion of reliving the past too far removed from reality, to the point of denying a historical truth, thus inverting the initial objective of preservation and transmission?". How is it possible to assess the preservation and the accessibility of the cultural heritage, namely in museums as a knowledge space? To address these questions, we developed our methodology by analyzing two interviews with representatives from immersive museums that employ diverse technologies and techniques for comparable goals: the creation and establishment of an immersive museum. We conducted an interview with the TNMOC app immersive museum, which resulted from a collaboration between The National Museum of Computing in Milton Keynes (United Kingdom) and the company in charge of creating Version 1 of the immersive tool. The purpose is to show their relevance and evaluate the accessibility to a tangible cultural heritage and its preservation with as special focus on immersive museums. We highlight the assets, the limitations and challenges ahead.